Application of three-dimensional graphene in sound generation via thermoacoustics - Ngoh, Zhi Lin (Nanyang Technological University, 2021)
Piezoelectric transducers are currently being used in sound generation applications such as medical ultrasound, ultrasound cleaners, microwave imaging and Sound Navigation and Ranging (SONAR). However, piezoelectric transducers have a small operating frequency band and large material size is required for low frequency sound generation. Thermoacoustics, on the other hand, is a non-mechanical sound generation method with a broad operating frequency band with potential to be an alternative sound transmitter. Its size independent acoustic frequency allows for utilization of small-size materials at low frequencies. Similar to piezoelectric transducers, material selection is important for effective utilization of sound generation. A good material candidate for such acoustic technique needs to have low electrical resistance for electrical current to pass through and Joule heating to occur, large surface area to maximize interactions with its surrounding medium, high thermal conductivity (κ) for uniform heat distribution and fast heat dissipation, and low specific heat capacity (Cp) for minimum heat storage. Carbon is a good base material due to its properties. Especially carbon nanostructured materials, which possess many favorable properties (electrical resistance of 2 – 2200 Ω, thermal conductivity of 200 – 5000 W·m-1·K-1, specific heat capacity of 0.71 – 0.74 J·g-1·K-1). Among various carbon nanostructured materials, three-dimensional graphene (3D-C) has interesting properties which provide it the potential to emit sound most efficiently. Its high porosity provides more surface contact with its surrounding medium allowing for fast thermal dissipation, and steep temperature gradients. At present, most studies have only investigated the effect of power input, output acoustic frequency and receiver-sample distance on measured sound pressure levels (SPLs) of 3D-C. Other key critical factors pertaining to the physical and chemical properties of 3D-C, such as connection method, acoustical backing, length, width, height, pore per inch (ppi) and macro-density, as well as the addition of reduced graphene oxide (rGO) and hexagonal boron nitride (h-BN), which can potentially impact 3D-C’s generated SPLs and operating temperatures warrants a study. The effect of these properties were hence investigated in this thesis. The initial part of the thesis covers 3D-C synthesized on nickel foams via thermal chemical vapor deposition (TCVD), with their crystal quality verified by Raman spectroscopy. With a Modulated Differential Scanning Calorimeter (MDSC), Cp was measured to be 0.68 J·g-1·K-1, lower than reported values of CNTs (0.72 – 0.75 J·g-1·K-1) and graphite (0.72 J·g-1·K-1). This indicates its potential to emit sound with greater efficiency than its predecessors. A lab-based acoustic set-up was built to conduct experiments for validation of various hypothesis and acoustical measurement standards were established to ensure consistency during inter-experimental comparison. Influence of acoustic frequency and electrical input power were also investigated. Increasing the acoustic frequency and electrical input power of 3D-C increases the generated SPLs as increasing these parameters result in faster oscillations of 3D-C’s surrounding medium. These results were validated by previous conducted studies with the same linear relationship observed. Changes were also made to 3D-C’s physical properties to understand their effect on emitted SPL. The dimensions of 3D-C as a whole material, namely length and width, do not affect SPL. An increase in material size by 50 % and 150 % increases electrical resistance by 30 % and 95 % respectively, which would theoretically induce more Joule heating. This increase, however, resulted in increased material volume, and hence not result in a higher SPL generation. Increasing material contact surface with its medium by increasing porosity by 20 pores per inch (ppi) would, in theory, cause an increase in contact surface area by 40 %, improving thermal dissipation and sound generation. This increase, however, was negated by an increase in material thickness by 3 mm, resulting in a similar amount of material present per millimeter. Increase in contact surface area induced by ppi change however does increase 3D-C’s cooling rate by 200 %. Increasing 3D-C’s growth time doubled material density, resulting in an increase in Cp by 27 times. This indicates an increase in the material’s heat storage capacity, causing a decrease in induced temperature gradient, leading to a decrease in SPL generation by ~30 dB. Increasing material density by compressing 3D-C to half its height, on the contrary, results in a ~5 dB increase in SPL at acoustical frequencies above 20 kHz due to additional constructive interference induced by compression. Therefore, to achieve maximum thermoacoustic sound generation, 3D-C has to have high porosity and low density and thickness. The effect of the addition of rGO and h-BN on 3D-C’s thermoacoustic effect were investigated concurrently. Random deposition of rGO sheets covered 3D-C’s pores, reducing its contact surface area with its surroundings and thermal dissipation, thereby reduced its sound generation by ~10 dB as compared to pure 3D-C. h-BN, an electrically insulating material with similar crystal structure to graphite, was coated on the surface of 3D-C to improve thermal dissipation. However, the deposition of h-BN resulted in a SPL reduction of ~5 dB due to the graphene being defective after h-BN deposition. The hybridization of h-BN with 3D-C (3D-BNC), allowed for the changing of the material electrical resistance based on material composition. For example, 30 × 20 × 2 mm3 3D-C had an electrical resistance of 2.5 Ω, while 30 × 20 × 2 mm3 3D-C with a chemical composition of 75 % 3D-BN and 25 % 3D-C had an electrical resistance of 85 Ω and 30 × 20 × 2 mm3 3D-C with a chemical composition of 50 % 3D-BN and 50 % 3D-C has an electrical resistance of 100 Ω for 3D-BNC. This resulted in more effective Joule heating and decreased the electrical input current required to generate sound by 55.6 % and 66.7 % respectively. A systematic study, varying test configuration and physical parameters of 3D-C and addition of h-BN and rGO sheets, had been conducted for optimization of 3D-C’s thermoacoustic performance. Additional studies, such as bending 3D-C during applicational use and increasing the range of acoustic frequency and input power, are recommended to be conducted to improve 3D-C’s efficiency for applicational use. 3D-BNC can be utilized in sound generation applications where impedance matching is required. A proof of concept of 3D-C’s ability to generate sound underwater was also demonstrated, which exhibits its potential to be utilized in SONAR with a broad frequency operation band.